White and Gray Matter Volume Changes and Correlation with Visual Evoked Potential in Patients with Optic Neuritis: A Voxel-Based Morphometry Study - Huang, Xin (Med Sci Monit, 2016)
BACKGROUND: The aim of this study was to investigate potential morphological alterations of gray and white matter in patients with optic neuritis (ON) and their relationship with behavioral performance, using voxel-based morphometry (VBM). MATERIAL/METHODS: Twelve (4 males, 8 females) patients with ON and 12 (4 males, 8 females) age-, sex-, and education-matched healthy controls (HCs) underwent magnetic resonance imaging (MRI). Imaging data were analyzed using two-sample t tests to identify group differences in gray and white matter volume (GMV, WMV). Correlation analysis was used to explore relationships between observed GMV and WMV of different areas and visual evoked potential (VEP) in ON. RESULTS: Compared with HCs, ON patients had: significantly decreased GMV in the left postcentral gyrus, left inferior frontal gyrus, left anterior cingulate, left and right middle frontal gyrus, and right inferior parietal lobule; decreased WMV in the left middle frontal gyrus, right superior frontal gyrus, left precentral gyrus and right inferior parietal lobule; and increased WMV in the left fusiform gyrus and left inferior parietal lobule. VEP latency of the right eye in ON correlated positively with WMV signal value of the left fusiform gyrus (r=0.726, p=0.008), and negatively with GMV signal value of the right inferior parietal lobule (r=−0.611, p=0.035). Duration of ON correlated negatively with WMV signal value of the right superior frontal gyrus (r=−0.662, p=0.019), while best-corrected visual acuity (VA) of the right eye correlated negatively with WMV signal value of the left middle frontal gyrus (r=−0.704, p=0.011). CONCLUSIONS: These results suggest significant brain involvement in ON, which may reflect the underlying pathologic mechanism. Correlational results demonstrate that VEP in ON is closely associated with WMV and GMV atrophy in many brain regions.